(y+5)(y+3)=(y+1)

Simple and best practice solution for (y+5)(y+3)=(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+5)(y+3)=(y+1) equation:



(y+5)(y+3)=(y+1)
We move all terms to the left:
(y+5)(y+3)-((y+1))=0
We multiply parentheses ..
(+y^2+3y+5y+15)-((y+1))=0
We calculate terms in parentheses: -((y+1)), so:
(y+1)
We get rid of parentheses
y+1
Back to the equation:
-(y+1)
We get rid of parentheses
y^2+3y+5y-y+15-1=0
We add all the numbers together, and all the variables
y^2+7y+14=0
a = 1; b = 7; c = +14;
Δ = b2-4ac
Δ = 72-4·1·14
Δ = -7
Delta is less than zero, so there is no solution for the equation

See similar equations:

| w-144=-144 | | 1.5x(x)=30 | | 1.5x*x=30 | | 49x-52=6(7x-8)+7x-4 | | b-23=50 | | 3x+0.10=2x-0.15 | | 9(x-3)/3=3(x+5)/9 | | 110=2(7=2w)=2w | | 4(7-2n)+5n=3(5n+21)+1 | | 16/7x=8/21 | | -1.4x=4(x+2.19) | | (x+5)(x+7)=(x-3)(x-12) | | 7(x-2)-4x=110 | | 7-2n=5n+21 | | 25/3=y | | -3(5t-4)+2t=4t-9 | | -4(5t-4)+5t=4t-5 | | 124=34m | | 6-4n=-6 | | 8v-4=5+8v | | 8v-8v=5-3 | | -2y-11=3y+19 | | (x+4)=x+(x+2)+(x+4)-2 | | 1/3=m+1/4 | | 2.5t+7.7=4.7 | | 2.5t+4.7=7.7 | | 7/8x-9/16=-1/2 | | 3y-7+y+47=5y+40-3y | | (x+1)=2x+15 | | x=3(-x)+68 | | 6-8y=70 | | 3+2(8x-9)=5x-26 |

Equations solver categories